Fusarium head blight resistance in U.S. winter wheat cultivars and elite breeding lines - Jin, Feng; Zhang, Dadong; Bockus, William W.; Baenziger, P. Stephen; Carver, Brett; Bai, Guihua (My University, 2013)
Fusarium (Fusarium graminearum) head blight (FHB) is a destructive disease of wheat (Triticum aestivum L.) worldwide. To characterize FHB resistance in U.S. wheat germplasm, 363 U.S. winter wheat accessions were repeatedly evaluated for FHB resistance. A high correlation (r =0.73, P < 0.001) for mean percentages of symptomatic spikelets (PSS) was observed between greenhouse and field experiments. The majority of tested accessions were either moderately or highly susceptible; only 7% of the accessions in the greenhouse and 6% of the accessions in the field showed a high level of resistance. Mean PSS for 19 accessions that carry markers for Fhb1, a major quantitative trait locus (QTL) from ‘Sumai3’, are 29.8% in the greenhouse and 25.1% in the field experiments. Fifty-four wheat accessions lacking Fhb1 showed at least a moderately high level of FHB resistance in the greenhouse and/or field. These included three resistant accessions, 35 moderately resistant accessions, and 16 accessions that showed different levels of resistance in greenhouse and field experiments. Accessions without Fhb1 that showed consistent resistance in both field and greenhouse experiments may be good sources for pyramiding native resistance QTLs from U.S. wheat with Fhb1.
Citation: Jin, Feng, Dadong Zhang, William Bockus, P. Stephen Baenziger, Brett Carver, and Guihua Bai. “Fusarium Head Blight Resistance in U.S. Winter Wheat Cultivars and Elite Breeding Lines.” Crop Science 53, no. 5 (2013): 2006–13. https://doi.org/10.2135/cropsci2012.09.0531.
Keywords: Fusarium graminearum; Fusarium head blight; Wheat